Validitas Penuntun Praktikum Biologi Berbasis Pendekatan Saintifik untuk Kelas XI SMA Semester I - Riska Ulandari; Ganda Hijrah Selaras; Heffi Alberida; Relsas Yogica (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Giving hands-on experience is very important in learning biology. One of the ways to provide direct experience is through practicum activities, so that the method used to guide and direct students in practical activities is by using a biology practicum guide. Based on the observations that have been made, it is known that the practicum guide used is still very simple, has not applied aspects of a scientific approach that are in accordance with the demands of the 2013 curriculum. This type of research is development research (R&D) which aims to produce a scientific approach-based biology practicum guide for class XI SMA semester I valid. This study uses a four-D development model. Based on the validation that has been done, the results obtained an average value of 85.56% with very valid criteria. So, it can be concluded that the biological guide based on the scientific approach that has been developed is valid and suitable to be used as a guide in practical activities. Practical activities play an important role in learning biology. One component that helps the process of practicum activities is a practicum guide. Based on the observations that have been made, it is known that the practicum guide used is still very simple, has not applied aspects of a scientific approach that are in accordance with the demands of the 2013 curriculum. This type of research is development research (R&D) using 3 stages of the 4-D development model (four -D models). The practicum guide developed was validated by two biology lecturers and one biology subject teacher. The instrument used in this study was a validity test questionnaire. The data analysis technique used is quantitative and qualitative descriptive analysis. Based on the validation that has been done, the results obtained an average value of 85.56% with very valid criteria. So, it can be concluded that the biological guide based on the scientific approach developed is valid and suitable to be used as a guide in practical activities.